An investigation of thrust, depth and the impedance cardiogram as measures of cardiopulmonary resuscitation efficacy in a porcine model of cardiac arrest. (November 2015) - Howe, Andrew; O'Hare, Peter; Crawford, Paul; Delafont, Bruno; McAlister, Olibhear; Di Maio, Rebecca; Clutton, Eddie; Adgey, Jennifer; McEneaney, David
Abstract: Objective: Optimising the depth and rate of applied chest compressions following out of hospital cardiac arrest is crucial in maintaining end organ perfusion and improving survival. The impedance cardiogram (ICG) measured via defibrillator pads produces a characteristic waveform during chest compressions with the potential to provide feedback on cardiopulmonary resuscitation (CPR) and enhance performance. The objective of this pre-clinical study was to investigate the relationship between mechanical and physiological markers of CPR efficacy in a porcine model and examine the strength of correlation between the ICG amplitude, compression depth and end-tidal CO2 (ETCO2 ). Methods: Two experiments were performed using 24 swine (12 per experiment). For experiment 1, ventricular fibrillation (VF) was induced and mechanical CPR commenced at varying thrusts (0–60 kg) for 2 min intervals. Chest compression depth was recorded using a Philips QCPR device with additional recording of invasive physiological parameters: systolic blood pressure, ETCO2, cardiac output and carotid flow. For experiment 2, VF was induced and mechanical CPR commenced at varying depths (0–5 cm) for 2 min intervals. The ICG was recorded via defibrillator pads attached to the animal's sternum and connected to a Heartsine 500P defibrillator. ICG amplitude, chest compression depth, systolic blood pressure and ETCO2 were recorded during each cycle. In both experiments the within-animal correlation between the measured parameters was assessed using a mixed effect model. Results: In experiment 1 moderate within-animal correlations were observed between physiological parameters and compression depth ( r = 0.69–0.77) and thrust ( r = 0.66–0.82). A moderate correlation was observed between compression depth and thrust ( r = 0.75). In experiment 2 a strong within-animal correlation and moderate overall correlations were observed between ICG amplitude and compression depth ( r = 0.89, r = 0.79) and ETCO2 ( r = 0.85, r = 0.64). Conclusion: In this porcine model of induced cardiac arrest moderate within animal correlations were observed between mechanical and physiological markers of chest compression efficacy demonstrating the challenge in utilising a single mechanical metric to quantify chest compression efficacy. ICG amplitude demonstrated strong within animal correlations with compression depth and ETCO2 suggesting its potential utility to provide CPR feedback in the out of hospital setting to improve performance.